Analysis of the population-level impact of co-administering ivermectin with albendazole or mebendazole for the control and elimination of Trichuris trichiura. Issue 2 (June 2016) - Turner, Hugo C.; Truscott, James E.; Bettis, Alison A.; Hollingsworth, T. Déirdre; Brooker, Simon J.; Anderson, Roy M.
Abstract: Introduction: Soil-transmitted helminth (STH) infections are predominately controlled by providing children with preventive chemotherapy with either albendazole or mebendazole. However, neither has a high efficacy against Trichuris trichiura . This low efficacy limits the overall effectiveness of the current STH control programmes against T. trichiura . It has been demonstrated that co-administering ivermectin with albendazole or mebendazole significantly increases the efficacy of current treatments, which may increase the overall effectiveness of control programmes. Methods: Using a STH transmission mathematical model, we evaluated the potential impact of co-administering ivermectin with albendazole or mebendazole to treat T. trichiura within a preventive chemotherapy programme targeting children (2–15 year olds). We evaluated the impact in terms of reduction in prevalent infections, mean worm burden, and prevalence of heavy infections. Results: Although the current treatment strategy reduced T. trichiura worm burden and prevalence of heavy infections, due to their poor efficacy the long term impact of preventive chemotherapy for children was smaller compared to the other STH. Co-administering ivermectin increased the projected impact of the preventive chemotherapy programme in terms of all three of the explored metrics, practically in high transmission settings. Furthermore, ivermectin co-administration greatly increased the feasibility of and timeframe for breaking transmission. Conclusions: Co-administering ivermectin notably increased the projected impact of preventive chemotherapy in high transmission settings and increased the feasibility for breaking transmission. This has important implications for control programmes, some of which may be shifting focus from morbidity control to interruption of transmission, and some of which may be logistically unable to provide preventive chemotherapy twice a year as recommended. However, the benefit of co-administering ivermectin is limited by the fact that 2–5 year olds are often ineligible to receive treatment. Highlights: The impact of chemotherapy against Trichuris is smaller compared to what can be seen for the other soil-transmitted helminths. Co-administering ivermectin increases the projected impact of preventive chemotherapy. It also has the potential to interrupt transmission in some settings.